La batalla de Madrid : (Noviembre 1936) / [redacción Javier Redondo... (et al.)] - Redondo Rodelas, Javier (La guerra civil Española mes a mes ; 7)
Contiene "Semblanzas" de : Juan García Oliver, Pedro Muǫz Seca, Buenaventura Durruti, Vicente Aleixandre, José Bardasano, Menéndez Pidal, José A. Primo de Rivera, Ricardo Sanz